IMPLEMENTASI MODEL INQUIRI SEBAGAI UPAYA MENINGKATKAN BERPIKIR KRITIS SISWA KELAS XI IPS DI SMA NEGERI 7 YOGYAKARTA PADA MATA PELAJARAN SOSIOLOGI - Edy Purwanto; Linda Nur Ramly; Andi Nugraha (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractThe aim of the research is to improve the students’ critical thinking. Themethod employed is classroom action research by implementing inquiry learning.This action research consists of three cycles, each of which includes the steps ofplanning, acting, observing, and reflecting. The subjects of the research are the gradeXI students of State Senior High School 7 YOGYAKARTA. The findings have shown thatthe students learn more actively and creatively.